Pollution and road infrastructure in cities of the People's Republic of China - Zhi Luo; Guanghua Wan; Chen Wang; Xun Zhang (Asian Development Bank Institute (ADBI), 2017)
Urban road infrastructure is crucial in determining air pollution. Yet, little is known about the roles played by road width vs. road length. This paper attempts to fill this gap by estimating the effects of road infrastructure on 10-micron particulate matter (PM10) using city-level data from the People's Republic of China (PRC). Our robust modeling results show that the road density index, defined as the ratio of surface area of roads to city territory size, is negatively correlated with PM10. More importantly, when the index of road density is decomposed into road width and road length components, the width is found to help reduce PM10, whereas the length is positively correlated with PM10, although the latter relationship is statistically insignificant.
Keywords: L92; Q53; R41; R53; 330; urban infrastructure; PM10 pollution; road length; road width; People's Republic of China